Phonosemantic Expression Of Size - Mamarasulova Maftuna Rustam qizi (International Journal Of Literature And Languages, 2025)
This article analyzes the characteristics of phonosemantics in expressing the category of volume measurement. The study highlights the role of acoustic and articulatory properties of vowel sounds in symbolically representing the size features of objects, based on theoretical and experimental sources. Summarizing the research of S.V. Voronin, O. Jespersen, E. Sapir, J. Ohala, A. Shinohara, and S. Kavahara, it is shown that phonosemantic regularity has universal characteristics inherent in different languages. The opposition of big - small in the Uzbek language and semantically related adjectives such as large, huge, tiny, and minute are analyzed from the perspective of their phonetic composition. The tendency of wide vowels to express the meaning of largeness and narrow vowels to express smallness is substantiated. Additionally, the presence of phonosemantic exceptions such as mayda (small), yirik (large), big, and small indicates the probabilistic, statistical nature of volume measurement meaning. The research results confirm the existence of phonosemantic foundations for the category of volume in the lexicon of the Uzbek language and highlight the importance of acoustic factors in the formation of meaning in language units.